Productivity and stability of sweet sorghum in the municipality of Cáceres-MT (Research, Society and Development, 2022)
Sweet sorghum is characterized by having broth rich in fermentable sugars that can be used in the off-season of sugarcane. However, for the recommendation of cultivars, it is necessary to perform performance studies, associated with the stability analysis. The objective of the research was to evaluate the performance of sweet sorghum genotypes, to study the Genotype x Environment (GxA) interaction and to verify the stability of the genotypes in order to select the most promising in the municipality of Cáceres-MT. 16 genotypes cultivated in 2013/2014 and 2014/2015 were considered, under a randomized block design with three replications. A joint ANOVA analysis of variance was performed to assess the significance of the GxA interaction and the stability study by the methods of Lin and Binns and Plaisted and Peterson. To group the genotypes, the Scott-Knott method was used. When grouping the genotypes the best performances were CMSXS644 and CV568 in environment one, and CMSXS643 and Sugargraze for environment two. For stability, the Plaisted and Peterson method recommends BRS509, CV568 and V82392, with high stability, but these did not present the best productive performance. For the method proposed by Lin and Binns, the genotypes with superior performance were CMSXS647, CMSXS630 and BRS511 in favorable environments and CMSXS643, BRS506 and CMSXS630 for unfavorable environments, such as the most productive and stable genotypes. The most promising genotypes were CMSXS643 and CMSXS647.